Functional outcome and quality of life following treatment for post-traumatic osteomyelitis of long bones - Zayzan, Khairul Rizal; Mohd Yusof, Nazri; Sulong, Ahmad Fadzli; Zakaria@Mohamad, Zamzuri; Ab Rahman, Jamalludin (Singapore Medical Association (SMA), 2020)
Introduction: The clinical outcomes and factors associated with treatment failure of post-traumatic osteomyelitis have been investigated by many studies. However, limb functionality and quality of life following treatment for this condition have not been thoroughly studied. Methods: This was a cross-sectional study that included 47 patients with post-traumatic osteomyelitis of the lower limb. Functional outcome was assessed using the Lower Extremity Functional Score (LEFS), and quality of life was assessed using the validated Malay version of Short Form-36 version 2. Results: Mean follow-up time was 4.6 (range 2.3–9.5) years. Median age was 44 years. Osteomyelitis was located in the tibia for 26 patients and in the femur for 21 patients. Osteomyelitis was consequent to internal infection in 38 patients and due to infected open fractures in nine patients. 42 (89.4%) patients had fracture union and control of infection. Bone defect was found to be a significant contributing factor for treatment failure (p = 0.008). The median LEFS for the success group was 65 when compared to 49 for the failure group. Although the success group showed better scores with regard to quality of life, the difference between the two groups was not statistically significant. Conclusion: The success rate for post-traumatic osteomyelitis of the lower limb was high. The presence of a bone defect was associated with treatment failure. Successfully treated patients had significantly better functional outcomes than failed ones.